A Comparison of Smokers, Non-Smokers, and Those Undergoing Treatment in Terms of Attitudes on Coping with Stress and Psychological Resilience - Acar, Sevda; Şaşman Kaylı, Derya; Yararbaş, Görkem (Addicta: The Turkish Journal on Addictions, 2019)
This study compares the attitudes on resilience and coping with stress of smokers, non-smokers, and those undergoing smoking-cessation treatment. This study involves three study groups: 116 people who applied to the Institute on Drug Abuse, Toxicology, and Pharmaceutical Science’s Smoking Cessation Polyclinic in Ege University to stop smoking, 110 smokers, and 121 non-smokers. The individual information form has been prepared in order to measure the variables of gender, age, and education level. In addition to the individual information form, the Fagerström Test for Nicotine Dependence, the Brief Coping Styles Inventory (Brief COPE), and the Resilience Scale for Adults have been used. The Kruskal-Wallis and MannWhitney U tests have been utilized in addition to descriptive statistics in analyzing the obtained data. Based on multiple comparisons among the three groups, significant differences among the groups have been obtained in certain sub-dimensions for the variables in coping strategies and resilience, as well as significant differences between smokers and the other groups in terms of their levels of resilience. To